Analysis Of Financial Performance Of Consumer Goods Industry Sector Companies Listed On The Idx In 2020-2022 - Sari, Hanna Ratna; Kurniawati, Susilaningtyas Budiana (STIE AMKOP, 2024)
This research aims to determine the effect of profitability, liquidity, solvability and activity ratios on financial performance of companies in the consumer goods industry sector listed on the IDX in 2020-2022. The method chosen is a quantitative research method because it deals with numbers. Samples taken with purposive sampling technique, this technique is obtained with certain characteristics. The sample obtained was 60 companies. Descriptive statistical analysis and multiple regression analysis used in the process of checking this data. The research results state that partially profitability, liquidity, solvability and activity ratios influence financial performance. Simultaneously profitability ratios, liquidity ratios, solvitability ratios and activity ratios influence financial performance. Keywords: Profitability; Likuidity; Solvability; Activity; Financial Performance